Perancangan Aplikasi Pengelolaan Data Karyawan Pada Perkebunan Kelapa Sawit Berbasis Android Mengunakan Metode Waterfall - Ikhsan Akbar; Agus Suhendar (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The main purpose of making this system to help KUD Sedyo Mulyo in managing employee data more efficiently and effectively. Palm Oil Employee Data Collection Information System must be developed and implemented. The oil palm plantation company KUD Sedyo Mulyo will be the subject of a case study that will be used in this research. KUD Sedyo Mulyo currently faces a number of problems in managing employee data. Some of the problems include data collection, maintenance, and manual processing of employee data. As a result, an information system that can assist them in overcoming these problems is needed. Requirement analysis, system design, software development, and implementation are the methodologies that will be used in this research. KUD Sedyo Mulyo will find specific needs in this case to start the needs analysis stage of the worker registrar. Next, the system design is done. This includes building the database, user interface, and system features. After the system design is complete, software development is carried out that meets the specifications. After that, the system will be tried out at the KUD Sedyo Mulyo production site and tested to ensure that it is successful. This research will produce an application for Palm Oil Employees that will help KUD Sedyo Mulyo manage its employee data more efficiently and effectively. With this system, KUD Sedyo Mulyo will be able to perform data collection, maintenance, and processing automatically, which will reduce human errors and optimize the use of resources